Review Literatur: Kemitraan Konservasi sebagai Upaya Pemberdayaan Masyarakat Desa Rantau Malam : Literature Review: Conservation Partnership as an Effort to Empower the Rantau Malam Village Community - Mutya, Ana Setiyati; Abetriawan, Ardhy; Ardin, Ardin; Azizah, Azizah (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Conservation partnerships serve as a platform for local communities around forests to empower themselves and build cooperation with conservation area managers. This research aims to identify the forms of conservation partnerships that are established between the communities of Rantau Malam Village and the Bukit Baka Bukit Raya National Park, the activities carried out in the conservation partnership, especially in the field of limited nature ecotourism, as well as the obstacles and supporting factors in the implementation of these partnership programs in Rantau Malam Village. The research method used a survey with interviews of 21 informants using a questionnaire guide, as well as direct observations in Rantau Malam Village, and a literature review using Google Scholar. The research results indicate that the form of partnership is in the form of granting access through the establishment of memoranda of understanding and cooperation agreements, as well as cooperation with the community in the form of empowerment and facilitation. The supporting and inhibiting factors analyzed based on communication variables, resources, disposition, and bureaucracy have progressed well, but still require improvements to optimize implementation. In conclusion, the implementation of the conservation partnership program in managing the National Park area alongside Farmer Groups has been progressing and has produced several actors from the conservation farmer groups, although it is not yet fully optimal and many aspects still need improvement. Technical guidance through socialization and the execution of the partnership program has been very effective.